A numerical algorithm for finding solutions of a generalized Nash equilibrium problem - Matioli L.C. (2012)
The work was partially supported by the CNPq, CAPES, and Foundação Araucária, Brazil, CONCYTEC (projects STIC-AMSUD), Peru and Fundación Carolina and CRM, Spain.